Studies on the proximate, mineral composition and role of winged bean in the agro ecosystem - V.SAIPRIYA,; P.SIDDHURAJU, (International Journal of Pharma and Bio Sciences, 2019)
The safest, nutritious and wholesome food for poor and the role of leguminous plants in the Agro ecosystem are the components resulted in the search for inexpensive and reliable alternative sources of protein of plant origin. Legumes compromising both commercial and wild species have played a significant role as part of traditional diets in most of the indigenous populations around the world. Hence the present study is focused to evaluate the Proximate composition and mineral profile of raw and differentially processed legume, Winged bean (Psophocarpus tetragonolobus). These indigenous legumes might have high potential to be used as human food to overcome the malnutrition-associated problems in developing countries and also for future commercial exploitation such as a source of nutraceuticals, for new food formulations as well as for use in the pharmaceutical industry. The unique distributions of functional components in these plants make them intriguing candidates for further research into their traditional medicinal uses. Different traditional, cost effective and more affordable processing methods are adopted base d on the indigenous knowledge system to assess their influence on nutritive value. Different part s of winged bean were studied for proximate composition using standard analytical methods. Mineral elements were analyzed using Nexion 300 X-ICP-MS (Inductively Coupled Plasma-Mass Spectrometer).Current study proposes that Further utilization prospectus of the Winged bean could be exploited and advocated for wider consumption and conservation in rural vicinity.